Artificial neural networks in biological and environmental analysis - Hanrahan, Grady (Boca Raton, Fla. : CRC Press, 2011)
"Drawing on the experience and knowledge of a practicing professional, this book provides a comprehensive introduction and practical guide to the development, optimization, and application of artificial neural networks (ANNs) in modern environmental and biological analysis. Based on our knowledge of the functioning human brain, ANNs serve as a modern paradigm for computing. Presenting basic principles of ANNs together with simulated biological and environmental data sets and real applications in the field, this volume helps scientists comprehend the power of the ANN model to explain physical concepts and demonstrate complex natural processes"--
ch. 1. Introduction -- ch. 2. Network architectures -- ch. 3. Model design and selection considerations -- ch. 4. Intelligent neural network systems and evolutionary learning -- ch. 5. Applications in biological and biomedical analysis -- ch. 6. Applications in environmental analysis.
Includes bibliographical references and index.
Also available as an electronic resource.
Keywords: Artificial intelligence -- Biological applications; Biology -- Data processing; Environmental engineering -- Data processing; Neural networks (Computer science) -- Scientific applications